Turbulence and Flow-Sediment Interactions in Open-Channel Flows - Gaudio, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The main focus of this Special Issue of Water is the state-of-the-art and recent research on turbulence and flow-sediment interactions in open-channel flows. Our knowledge of river hydraulics is deepening, thanks to both laboratory/field experiments related to the characteristics of turbulence and their link to erosion, transport, deposition, and local scouring phenomena. Collaboration among engineers, physicists, and other experts is increasing and furnishing new inter-/multidisciplinary perspectives to the research of river hydraulics and fluid mechanics. At the same time, the development of both sophisticated laboratory instrumentation and computing skills is giving rise to excellent experimental-numerical comparative studies. Thus, this Special Issue, with ten papers by researchers from many institutions around the world, aims at offering a modern panoramic view on all the above aspects to the vast audience of river researchers.